Odpowiedzi

Najlepsza Odpowiedź!
2010-03-04T18:11:46+01:00
A) 3x-4(y-3x)
3x - 4y + 12x = -4y + 15x

b) 8(-12x+y)+12x
-96x + 8y +12x = -84x +8y

c) 3(a-3b)-4(2b-4x)
3a - 9b - 8b + 16x = 3a - 17b + 16x

d) -5(4a-3b)-4(5a-5b)
-20a + 15b - 20a +20b = -40a + 35b

e) -2x(x-5y-3)+3x(x+5y+2)
(wyrazy podobne z nawiasów się redukują?)
3x + 1

f) -3x(2x-3y)+2x(-3x-5y-1)
-2x - 7y - 1

26 3 26
2010-03-04T18:14:12+01:00
A)3x-4y-12x=-4y-9x
b)-96x+8y+12x = -84x + 8y
c)3a-9b -8b - 16x= 3a -17b - 16x
d)-20a -15b-20a -20b=-40a -35b
e)-2x(do kwadratu)-10xy -6x + 3x(do kwadratu)+15y +6x
17 3 17
2010-03-04T18:18:48+01:00
A) 3x-4y+12x=15x-4y
b) -96x+8y-12x=-84x+8y
c) 3a-9b-8b+16x=3a-17b+16x
d) -20a+15b-20a+15b=-40a+35b
e) -2x kwadrat + 10xy+6x +3x kwadrat+15xy+6x= x kwadrat +25xy+12
f) -6x kwadrat +9xy-6x kwadrat -10xy-2x=-12x kwadrat -xy-2x
24 4 24